Pengaruh Etika Uang, Religiositas, dan Materialisme Terhadap Penggelapan Pajak: Studi Kasus Wajib Pajak Orang Pribadi Yang Terdaftar di KP2KP Maba Kabupaten Halmahera Timur - Wa Ode Sindi Rahayu; Rinto Syahdan; Fitriani Sardju (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2024)
The research aims to find out the effect of money ethics, religiosity, and materialism on tax evasion. The population of this research is individual taxpayers who are registered at KP2KP (Counselling Service and Tax Consultation Office) Maba East Halmahera Regency, North Maluku Province. The data collection technique of this research used a questionnaire which was distributed directly to the respondents. Respondents in this research amounted to 373 respondents consisting of 188 male respondents and 185 female respondents. Data analysis was performed by using multiple linear regression. The results obtained from this research are that money ethics and religiosity have no effect on tax evasion while materialism has an effect on tax evasion. This research is expected to provide implications both theoretically and practically.